Association of diet and outdoor time with inflammatory bowel disease: a multicenter case-control study using propensity matching analysis in China - Chu, Xiaotian; Chen, Xuanfu; Zhang, Huimin; Wang, Yufang; Guo, Hong; Chen, Yan; Liu, Xiaowei; Zhu, Zhenhua; He, Yao; Ding, Xueli; Wang, Qunying; Zheng, Changqing; et al. (Frontiers in Public Health, 2024)
Author contributions: All authors contributed to the diagnosis, inclusion of the patients and data collection. Xiaotian Chu and Xuanfu Chen contributed to research design, data analysis and manuscript draft. Jiaming Qian and Hong Yang contributed to conceptualization and validation of this research. All authors reviewed and made critical revisions to the manuscript. The manuscript has been read and approved by all the authors. Ethical Disclosure: All procedures involving research study participants were approved by the Peking Union Medical College Hospital and the Chinese Academy Medical Science Ethics Committee (JS-347) and other medical centers. Written informed consent was obtained from all subjects.